Symplectin evolved from multiple duplications in bioluminescent squid - Francis, Warren R. (PeerJ, 2017)
The squid Sthenoteuthis oualaniensis, formerly Symplectoteuthis oualaniensis, generates light using the luciferin coelenterazine and a unique enzyme, symplectin. Genetic information is limited for bioluminescent cephalopod species, so many proteins, including symplectin, occur in public databases only as sequence isolates with few identifiable homologs. As the distribution of the symplectin/pantetheinase protein family in Metazoa remains mostly unexplored, we have sequenced the transcriptomes of four additional luminous squid, and make use of publicly available but unanalyzed data of other cephalopods, to examine the occurrence and evolution of this protein family. While the majority of spiralians have one or two copies of this protein family, four well-supported groups of proteins are found in cephalopods, one of which corresponds to symplectin. A cysteine that is critical for symplectin functioning is conserved across essentially all members of the protein family, even those unlikely to be used for bioluminescence. Conversely, active site residues involved in pantetheinase catalysis are also conserved across essentially all of these proteins, suggesting that symplectin may have multiple functions including hydrolase activity, and that the evolution of the luminous phenotype required other changes in the protein outside of the main binding pocket.